Development of agricultural drought evaluation system in Korea - Parsons, Larry R., author; Wheaton, T. Adair, author; Castle, William S., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
There are two ways to mitigate drought, structural and nonstructural measures. Structural measures include storage of irrigation water and development of emergency wells, nonstructural measures involve water saving management by early warning system. To predict and evaluate drought for agriculture, we need to develop drought indices. Presently, drought preparedness are be classified by precipitation, reservoir storage, soil moisture in paddy and upland, and the growing status of crops. However, the indices lack clear quantitative criteria for consistent judgment. Consequently, improvements are needed in selection and utilization of proper drought indices to warn of oncoming drought. The objectives of this study were to develop an Agricultural Drought Evaluation System, and to evaluate indices for current agricultural status using the system. We considered several existing drought indices for application to Korea: Reservoir Storage Index (RSI), Standardized Precipitation Index (SPI), Mean Rainfall Index (MRI), Dry Day Index (DDI), Palmer Drought Severity Index (PDSI), Crop Moisture Index (CMI), Percent of Normal, Deciles, and Percent of Median. We determined that four indices are applicable to Korea RSI, SPI, MRI and DDI. The Agricultural Drought Evaluation System was developed using these four indices to analyze temporal drought status.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.